Hubungan Pendidikan dan Pengetahuan dengan Perilaku Manajemen Diri Diabetes Melitus Tipe 2 - Hertuida Clara (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2018)
Patients with type 2 Diabetes Mellitus are at risk for complications including acute complications and chronic complications. It is estimated that diabetes is the leading cause of death worldwide with a global prevalence of 552 million. To prevent the occurrence of complications above, it is necessary to control diabetes through the implementation of correct and regular self management behavior every day. The aim of the study was to identify the relationship between the level of education and knowledge with the behavior of self-management of patients with type 2 Diabetes Mellitus. The study design used was cross sectional, with a sample of 112 respondents. Measuring instruments used are Diabetes Knowledge (DKN) Scale and Summary Diabetes Self Care Activity (SDSCA). The results showed a significant relationship between knowledge and self-management behavior (p value <0.001), so it can be concluded that self management behavior increases if patients with type 2 Diabetes Mellitus have good knowledge of DM self-management.